Lactylation’s role in bone health and disease: mechanistic insights and therapeutic potential - Ye,Zhiyuan; Chen,Xuanyu; Zou,Jiyuan; Wu,Wenjing; Yang,Jingyuan; Yang,Li; Guo,Lvhua; Luo,Tao (PeerJ, 2025)
This article reviews the mechanisms and research progress of lactylation, an emerging post-translational modification (PTM) of proteins, in bone metabolism and related diseases. Lactate-derived lactylation modifies lysine residues on histones, affecting chromatin structure and gene expression. Studies indicate that lactylation plays a significant role in bone metabolism, with mechanisms including the regulation of osteoblast differentiation, potential influence on osteoclast activity, and indirect effects on bone homeostasis through the modulation of immune cell functions such as macrophages and T cells. In periodontitis, lactylation may impact inflammation progression and tissue repair by regulating macrophage polarization and function. In osteoporosis, lactylation adjusts bone density by influencing osteogenic gene expression. Additionally, the role of lactylation in other skeletal behaviors and diseases is gradually being revealed, such as its association with insulin resistance in skeletal muscle, and its roles in tooth development and rheumatoid arthritis, providing new targets for the treatment of these conditions. Future research will focus on the enzymatic regulatory mechanisms of lactylation, its interactions with other PTMs, and its involvement in metabolic diseases and inflammatory responses. The regulation of lactylation offers new strategies for the treatment of bone-related diseases, including the development of drugs that can reverse or modulate lactylation, and the restoration of bone metabolic balance through the adjustment of lactylation levels. As the understanding of lactylation’s regulatory mechanisms and biological functions deepens, its potential for clinical applications will continue to expand, particularly in the fields of bone regeneration, immunity, and the treatment of metabolic diseases.
Keywords: Lactylation; Bone metabolism; Periodontitis; Osteoporosis